Prison literature and Palestinian cause in the poem of Samar Fi Al-Sijn By Tawfiq Ziyad - Nur Farhana Mohamad Zainol,; Nursafira Lubis Safian, (Penerbit Universiti Kebangsaan Malaysia, 2022)
This research analyzes the poem Samar fi al-Sijn by Palestinian poet Tawfiq Ziyad. It explores Tawfiq Ziyad’s personal experience during his detention with the community as well as to study how he used his poem to highlight the Palestinian issue and then defend his homeland. This study also aims at highlighting the opinions of the critics in interpreting the meaning of prison literature, since they come out with different interpretation. The study used the descriptive and analytical method, where it analyzed the content of the prison topic in the poem Samar fi al-Sijn. The study finally shows that prison literature is not only a creative writing written inside the prison, but rather a writing that dealt with the prison issue as well as the painful condition of prisoners, and the extent of their suffering behind the cell. The study also concluded that the poem Samar fi al-Sijn contains the prison issues as well as the elements of struggle and steadfastness that encourage all the Palestinian people to stand and liberate their homeland from the cruelty of the occupation.